1030 Charcot-Marie-tooth disease: genetic diagnoses in a specialist clinic. Issue 3 (9th February 2012) - Murphy, S; Pandraud, A; Liu, Y; Fawcett, K; Polke, J M; Davidson, G; Laura, M; Davis, M; Houlden, H; Reilly, M M
Abstract : The inherited neuropathies are a genetically and clinically heterogeneous group of disorders encompassing Charcot-Marie-Tooth disease (CMT), hereditary motor neuropathy (HMN) and hereditary sensory and autonomic neuropathy (HSAN). Mutations in over 45 genes have been implicated in causing the inherited neuropathies, and many more remain unknown. In order to determine the proportion of patients with inherited neuropathy attending our clinic who obtained a genetic diagnosis, we screened all known genes that cause CMT, HMN and HSAN. Of 871 patients attending a specialist neuropathy clinic over a 5-year period, 613 had an inherited neuropathy of whom 409 had CMT. A genetic diagnosis was reached in 59% of patients with CMT; 54% accounted for by chromosome 17 rearrangements or mutations in the commonly available genes PMP22, GJB1, MPZ and MFN2. A genetic diagnosis was achieved in 79% of patients with CMT1 and 35% of CMT2. The chromosome 17 duplication only accounted for 38% of CMT, less than reported in other populations; this reflects a bias in our clinic towards patients with rarer forms of CMT. We give details of the individual contributions the rarer genes made to our cohort. These results suggest that the majority of patients with CMT1 should obtain a genetic diagnosis. Mutations in the rarer known genes account for a small proportion of patients with CMT, and many genes for CMT2 remain unknown. We suggest an algorithm for genetic testing in patients with CMT in the UK.